Development of seawater reverse osmosis membranes for efficient desalination and boron removal - Li, Can (Nanyang Technological University, 2024)
The sustainable growth of industries and populations has increased freshwater consumption dramatically and thus, it is a great urgency to search for alternative water resources, such as via energy-efficient seawater desalination processes. Pressure-driven membrane desalination via seawater reverse osmosis (SWRO) has now evolved into the leading technology because of its relatively high energy efficiency compared to thermal desalination. To date, polyamide (PA) thin-film composite (TFC) membrane, which was prepared by interfacially polymerized reaction between amine and acyl chloride on the top of a microporous substrate, is the state-of-the-art SWRO membrane due to its inherently high scalability and stability. However, the TFC SWRO membrane is still plagued by some challenges, including a trade-off between water permeability and solute rejection, inadequate boron rejection, and others. Extensive research has been performed in recent decades to improve the selectivity of membranes and eliminate boron, aiming to enhance the energy efficiency and sustainability of seawater desalination through the utilization of innovative membrane preparation processes and comprehensive analysis involving interfacial polymerization and surface modification strategies. The main objective of this study is to explore feasible fabrication methods for designing PA layer with desirable properties and enabling SWRO membranes with efficient desalination and boron removal. Firstly, the roles of aqueous and organic co-solvents in the formation of PA film were elucidated to unveil their mechanistic distinctions underlying the development of co-solvent-mediated membranes exhibiting high water permeability and comparable selectivity for seawater desalination applications (Chapter 3). The homogeneous pre-deposition of E-coli-based nanovesicles onto the substrate was attempted using an economical spray-assisted technique and a regulated interfacial compatibility strategy followed with the interfacial polymerization process, aiming to develop a wrinkled PA SWRO membrane with higher permselectivity compared to the nanovesicles-free control membrane (Chapter 4). Additionally, the integration of fluorine-containing monomers in the fabrication of fluorinated PA SWRO membranes resulted in satisfactory water/salt selectivity and boron rejection, thereby endowing the membrane with superior separation efficiency compared to both the control and commercial SWRO membranes (Chapter 5). The aliphatic amine-modified PA SWRO membrane prepared using the proposed in-situ rapid construction protocol demonstrated exceptional boron removal efficiency of up to 90%, which may have significant implications for more efficient membrane-based seawater desalination and boron removal (Chapter 6). In summary, this thesis highlights the innovative design process and construction method for fabricating composite membranes suitable for seawater desalination applications based on a deep understanding of interfacial polymerization mechanisms and surface modification strategies. The re-designed PA selective layer, featuring distinct microstructure and chemical properties, can be leveraged on to fabricate high-efficiency membranes that may be capable of overcoming the permeability-selectivity tradeoff and insufficient boron removal.